(untitled) (Cardiovascular Journal, 2011)
Background: It has been reported that acute myocardial infarction preceded by angina has favorable short term outcome. To validate this in our setting, this study was undertaken in National Institute of Cardiovascular Diseases. Method: This is a prospective and observational study. 100 patients were evaluated for the short term outcomes of patients of AMI preceded by angina. Result : Observation showed that patients of AMI preceded by angina has less damage of the myocardium as evident by lower CK-MB values and better preservation of left ventricular function. It has also been shown that early complications like death, VT & VF, asystole, CHB, acute LVF, cardiogenic shock were significantly lower in patients of AMI preceded by angina than those without angina. Conclusion: It is observed that incidence of previous angina is an important independent predictor of outcome of the patients with myocardial infarction. Key words: AMI, Angina, Ischaemic heart Disease DOI: http://dx.doi.org/10.3329/cardio.v1i1.8204 Cardiovasc. j. 2008; 1(1):48-52